Facile and quick preparation of carbon nanohorn-based counter electrodes for efficient dye-sensitized solar cells - Lodermeyer, Fabian; Prato, Maurizio; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
For the first time, Pt-free counter electrodes based on carbon nanohorns for highly efficient dye-sensitized solar cells were assembled by a facile and fast drop cast technique. These novel electrodes feature an effective catalytic behavior towards the reduction of I3- and, as such, afford even higher short-circuit current densities compared to Pt-based references. In a final device, solar cells with 7.7% efficiency were achieved.
EAM Import::2019-03-14